Private sector availability and affordability of under 5 malaria health commodities in selected states in Nigeria and the Federal Capital Territory - Kunle Rotimi; Babatunde Fagbemi; Ademola Joshua Itiola; Taiwo Ibinaiye; Adaeze Aidenagbon; Chrysantus Dabes; Ahmed Aminu Biambo; Azuka Iwegbu; Sarah Onabajo; Chibuzo Oguoma; Olusola Oresanya (Journal of Pharmaceutical Policy and Practice, 2024)
Background To guarantee uninterrupted service delivery, quality-assured products must be affordable and continuously available across all sectors, including the private sector, which provides more than 60% of healthcare services in Nigeria. We investigated the private sector availability and affordability of under 5 malaria commodities to establish the level of access in this sector. Methods We surveyed patent medicine and pharmacy stores across seven states in Nigeria and the Federal Capital Territory to establish the availability and affordability of selected malaria commodities for children under 5 years. Availability was measured as the percentage of visited outlets with the product of interest on the day of visit, while affordability was assessed by establishing if it cost more than a day’s wage for the least-paid government worker to purchase a full course of malaria diagnostic test and/or medication. Results Artemisinin-based antimalarials for uncomplicated and severe malaria were the most available commodities. SPAQ1 and SPAQ2 used for seasonal malaria chemoprevention campaign were surprisingly also available in some outlets. However, only about half (48.3% and 53.3%) of the surveyed outlets had stock of artemether/lumefantrine (AL1) and artesunate injection, respectively. The median price of surveyed products ranged from USD (United States Dollars) 0.38 to USD 2.17 per treatment/test. Except for amodiaquine tablet and artemether injection, which cost less, all other originator brands cost the same or more than the lowest-priced generic. Antimalarial products were affordable as their median prices were not more than a day’s wage for the least-paid government worker. However, when the cost of testing and treatment with artemisinin-based combination therapies (ACTs) was assessed, testing and treatment with dihydroartemisinin/piperaquine were unaffordable as the they cost more than 1.5 times the daily wage of the least-paid government worker. Conclusion The overall private sector availability of under-five malaria commodities in surveyed locations was suboptimal. Also, testing and treatment with recommended ACTs were not affordable for all surveyed products. These findings suggest the need for interventions to improve access to affordable under-five malaria commodities.